Pembuktian Digital dalam Sengketa Perdata: Menguji Validitas Formil dan Materiil Dokumen Elektronik di Era Modern - Galuh Candra Utami; Sidi Ahyar Wiraguna (Referendum : Jurnal Hukum Perdata dan Pidana, 2025)
The rapid advancement of digital technology has fundamentally transformed civil legal interactions, making electronic documents such as instant messages, online transactions, and digital contracts primary forms of evidence in many civil disputes. However, their admissibility in judicial proceedings remains fraught with challenges concerning formal and material validity. This study aims to identify juridical and technical obstacles in digital evidence and to formulate an ideal model for civil procedural law that ensures reliable electronic proof. A normative-juridical approach with qualitative analysis was employed, combining doctrinal research through legislative review, jurisprudence, and scholarly literature with case studies of court decisions involving electronic evidence, particularly in divorce disputes. The findings reveal that inconsistent judicial treatment stems from the absence of specific procedural rules in Indonesia’s civil procedure framework still rooted in colonial-era HIR and RBg alongside limited digital infrastructure and low technological literacy among judicial actors. In response, the study proposes an integrated legal construction model featuring explicit provisions in the upcoming Civil Procedure Code, adoption of the functional equivalence principle, institutionalization of digital forensic experts in litigation, and procedural safeguards for vulnerable parties. The research concludes that only through holistic reform of the evidentiary paradigm can Indonesia’s civil justice system guarantee fairness, legal certainty, and relevance in the digital era.